In-situ at a distance? challenges and opportunities for health and place research methods in a post-COVID-19 world. (May 2021) - Shareck, Martine; Alexander, Stephanie; Glenn, Nicole M.
Abstract: In-situ methodologies, including go-along and photo-elicited interviews, are ideal for harnessing people's lived experiences of place and their meanings for health and health equity. Their immersive nature means that the COVID-19 pandemic has impacted their use. Physical distancing measures combined to anxiety over the sharing of physical space have created ethical and practical challenges to the conduct of in-person in-situ methodologies. However, in-situ methodologies are precisely needed to gain deeper understandings of people's changing relationships to place post-COVID-19. In this commentary we discuss emerging challenges, highlight questions researchers should ask before engaging in these methods in the future, and explore adaptations and alternatives to traditional in-person in-situ methodologies. Highlights: In-situ methods allow studying how lived experiences of place relate to health. In-situ methods are immersive, participatory and anti-oppressive. COVID-19 has created ethical and practical challenges for in-situ methods. Re-imagining in-situ methods is essential for post-COVID-19 health equity research. Virtual go-along and photo-elicited interviews are promising adaptations.